Infrastructure for sustainable development - Thacker, S; Adshead, D; Fay, M; Hallegatte, S; Harvey, M; Meller, H; O’Regan, N; Rozenberg, J; Watkins, G; Hall, J (Springer Nature, 2019)
Infrastructure systems form the backbone of every society, providing essential services that include energy, water, waste management, transport and telecommunications. Infrastructure can also create harmful social and environmental impacts, increase vulnerability to natural disasters and leave an unsustainable burden of debt. Investment in infrastructure is at an all-time high globally, thus an ever-increasing number of decisions are being made now that will lock-in patterns of development for future generations. Although for the most part these investments are motivated by the desire to increase economic productivity and employment, we find that infrastructure either directly or indirectly influences the attainment of all of the Sustainable Development Goals (SDGs), including 72% of the targets. We categorize the positive and negative effects of infrastructure and the interdependencies between infrastructure sectors. To ensure that the right infrastructure is built, policymakers need to establish long-term visions for sustainable national infrastructure systems, informed by the SDGs, and develop adaptable plans that can demonstrably deliver their vision.